The Impacts of the Segregation Wall on the Sustainability of Transportation Systems and Services in the Palestinian Territories - Sameer Abu-Eisheh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The Israeli occupation authorities started in April 2002 the construction of the segregation wall on confiscated Palestinian land for claimed security reasons, ignoring the international law which does not allow the occupier to do that. The Wall, when completed, will isolate parts located between the wall and the 1949 Armenistic Line, forming 46% of the total area of the West Bank. The results of the field study indicate that there will be severe impacts of the wall in the field of transportation. The wall will lead to severe deterioration in the Palestinians quality of life, as it will restrict the movement and free transportation for 647 thousand Palestinians forming one third the Palestinians living in the West Bank, including restricting their ability to reach their agricultural land. The wall cuts off public transportation lines for a number of communities which the wall isolates. The number of links connecting a community with others is reduced for many of the impacted communities, while about half the total length of the roadway network in the West Bank will lie behind the wall. The Israeli measures cause the length of, and travel time on, the roads connecting these impacted communities to at least double on the average, and therefore, result in a similar increase in travel cost. Therefore, the wall will affect the sustainability of the transportation systems and will prevent such systems from playing the role they should provide towards sustainable development in the Palestinian territories. The paper presents a number of recommendations to pressure the Israeli authorities to stop building the wall, and to assist the Palestinians living in the impacted areas in their struggle against the challenges they are facing, through means that lessen the negative impacts of the wall, especially those which affect the sustainability of the transportation systems.